Dlx-2 and glutaminase upregulate epithelial-mesenchymal transition and glycolytic switch - Lee, Su Yeon (Oncotarget, 2016)
Most cancer cells depend on enhanced glucose and glutamine (Gln) metabolism for growth and survival. Oncogenic metabolism provides biosynthetic precursors for nucleotides, lipids, and amino acids; however, its specific roles in tumor progression are largely unknown. We previously showed that distal-less homeobox-2 (Dlx-2), a homeodomain transcription factor involved in embryonic and tumor development, induces glycolytic switch and epithelial-mesenchymal transition (EMT) by inducing Snail expression. Here we show that Dlx-2 also induces the expression of the crucial Gln metabolism enzyme glutaminase (GLS1), which converts Gln to glutamate. TGF-β and Wnt induced GLS1 expression in a Dlx-2-dependent manner. GLS1 shRNA (shGLS1) suppressed in vivo tumor metastasis and growth. Inhibition of Gln metabolism by shGLS1, Gln deprivation, and Gln metabolism inhibitors (DON, 968 and BPTES) prevented Dlx-2-, TGF-β-, Wnt-, and Snail-induced EMT and glycolytic switch. Finally, shDlx-2 and Gln metabolism inhibition decreased Snail mRNA levels through p53-dependent upregulation of Snail-targeting microRNAs. These results demonstrate that the Dlx-2/GLS1/Gln metabolism axis is an important regulator of TGF-β/Wnt-induced, Snail-dependent EMT, metastasis, and glycolytic switch.